Pengaruh Resiliensi terhadap Psychological Well Being pada Mahasiswa Kedokteran Universitas Islam Bandung - Sekar Ayu Nurhandari Mulya; Agus Budiman (UNISBA Press, 2023)
Abstract. Psychological well-being is a condition of individuals who have a positive attitude towards themselves, can make their own decisions, regulate the environment according to their needs, have life goals, and try to develop themselves. (Ryff, 1989). It is important for medical students to have high psychological well-being because they will be recognized as